Reactive oxygen and iron species monitoring to investigate the electro-Fenton performances. Impact of the electrochemical process on the biodegradability of metronidazole and its by-products. (May 2018) - Aboudalle, Arwa; Fourcade, Florence; Assadi, Aymen Amin; Domergue, Lionel; Djelal, Hayet; Lendormi, Thomas; Taha, Samir; Amrane, Abdeltif
Abstract: In this study, the monitoring of reactive oxygen species and the regeneration of the ferrous ions catalyst were performed during electro-Fenton (EF) process to highlight the influence of operating parameters. The removal of metronidazole (MTZ) was implemented in an electrochemical mono-compartment batch reactor under various ranges of current densities, initial MTZ and ferrous ions concentrations, and pH values. It was found that under 0.07 mA cm −2, 0.1 mM of ferrous ions and pH = 3, the efficiency of 100 mg L −1 MTZ degradation and mineralization were 100% within 20 min and 40% within 135 min of electrolysis, respectively. The highest hydrogen peroxide and hydroxyl radical concentrations, 1.4 mM and 2.28 mM respectively, were obtained at 60 min electrolysis at 0.07 mA cm −2 . Improvement of the biodegradability was reached from 60 min of electrolysis with a BOD5 /COD ratio above 0.4, which was reinforced by a respirometric study, that supports the feasibility of coupling electro-Fenton and biological treatment for the metronidazole removal. Highlights: MTZ electroreduction involved in its degradation not in its mineralization. Good regeneration of ferrous ions up to 0.07 mA cm −2 Highest OH production for 0.07 mA cm −2, pH 3 and 0.1 mM of ferrous ions Limit of biodegradability reached for 60 min of electrolysis according to BOD5 test. Results from BOD5 reinforced by respirometric study implemented during 21 days.